Antitumor immunity by small extracellular vesicles collected from activated dendritic cells through effective induction of cellular and humoral immune responses. (September 2020) - Matsumoto, Akihiro; Asuka, Maho; Takahashi, Yuki; Takakura, Yoshinobu
Abstract: Dendritic cell-derived small extracellular vesicles (DC-sEVs) are proposed as a novel candidate for tumor antigen-based cancer immunotherapy. In order to improve the DC-sEV-induced antitumor immunity, production of DC-sEVs capable of inducing potent antigen-specific humoral and cellular immune responses is necessary. Here, we collected sEVs from DCs and added ovalbumin (OVA), which was used as model antigen, as well as LPS and IFN-γ, to prepare DC-sEVs with high immune activity. After confirming that the collected sEVs, named activated-DCOVA -sEVs, contained OVA and possessed immunologically relevant components (MHC class I molecule displaying antigen epitopes and co-stimulatory molecules, as well as sEV marker proteins), we found that activated-DCOVA -sEV stimulated macrophages and DCs through Toll-like receptor 4 signaling and boosted innate immunity in the tumor microenvironment. Moreover, activated-DCOVA -sEVs induced potent antigen-specific humoral and cellular immune responses both in vitro and in vivo . Finally, immunization with activated-DCOVA -sEVs exhibited stronger in vivo antitumor effects in tumor-bearing mice induced by inoculation with OVA-expressing tumor cells.